PRACTICING CONSCIOUS TIME-BINDING. - DAWES, MILTON (ETC: A Review of General Semantics, 2009)
The article discusses the concept of conscious time-binding, a term from the field general semantics meaning transmission of knowledge through culture. It is a technique in the discipline of general semantics, which seeks to develop ways of responding to events without personal distortion. Benefits of conscious time-binding cited include complementing learning from books with knowledge gained from life experience, developing sensory awareness, and thinking about how we think.